Effect of the time of application on the biocontrol efficacy of Pasteuria penetrans against root-knot nematode Meloidogyne incognita - R.K.Kaul1, K. K. Chaudhary1,2* and (Journal of Phytology, 2010)
Â In the present study, the effect of pre, post and simultaneous applications of Pasteuria penetrans to nematode Meloidogyne incognita was determined. Time of application of P. penetrans to soil was observed to have profound effect on the efficacy of the bacterium and it also affected the plant growth and multiplication of the nematode. The simultaneous application of P. penetrans infested soil with M. incognita J2 was found to be the most effective in the improving fresh and dry biomass of the chilli crop. This treatment was followed by the seven days prior application of P. penetrans to Nematode. The simultaneous application of P. penetrans with nematode treatment was found to cause maximum reduction in final population of M. incognita. This treatment yielded 45-53% improvement in the various parameters of the fresh and dry biomass of the crop and 71% reduction in final nematode population when compared with the control. Key words: Biocontrol, Pasteuria penetrans, Meloidogyne incognita, Time of application <span style="line-height: 110%; font-variant: normal !important; font-family: ";Book Antiqua";,";serif";; letter-spacing: -0.3pt; font-size: 7pt; font-weight: normal; mso-font-kerning: 0pt; mso-no-proof: no; mso-fareast-language: EN-SG; mso-ansi-language: EN-SG;" lang="EN-SG">K. K. Chaudhary and R.K.Kaul. Effect of the time of application on the biocontrol efficacy of Pasteuria penetrans against root-knot nematode Meloidogyne incognita. Â J Phytol 2/7 (2010) 70-74.